Long-Term Risks and Possible Benefits Associated with Late Adolescent Romantic Relationship Quality - Kansky, Jessica (J Youth Adolesc, 2018)
Adolescent romantic relationships have the potential to affect psychological functioning well into adulthood. This study assessed adolescent romantic relationship qualities as long-term predictors of psychological functioning utilizing a longitudinal multi-method, multi-informant study of 80 participants (59% female; 54% Caucasian, 35% African American, 11% mixed or other race) assessed at age 17 along with their romantic partners and at ages 25–27. Controlling for gender, family income, and baseline mental health, partner-reported hostile conflict at age 17 predicted relative increases in internalizing behaviors from age 17 to 27. In contrast, observed teen support with their partner during a help-seeking task at age 17 predicted relative decreases in externalizing behaviors over time. The results are interpreted as suggesting qualities that may help determine whether adolescent romances have positive vs. negative long-term psychological health implications.